Simulation and prediction of hydrodynamic performance at University of Zulia's wastewater stabilization ponds using a 3D-Computational Fluid Dynamic (CFD) model - Aldana, Gerardo; Bracho, Nibis (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The University of Zulia wastewater treatment is comprised for three series of stabilization ponds, 3 facultative (Al, B 1, C 1) and 6 maturation (A2, A3, B2, B3. C2, C3) which have been operational since 1992 when it was founded. A series of simulation and prediction of hydrodynamic behavior in WSPs using a model HYDRO-3D calibrated is the aim of this study. Two task stages conformed by 15 hydraulic model simulations were made in order to evaluate the hydraulic performance based on outputs vector plots. The former was simulated with the original lagoon design built in 1992, that included solely an inlet and an outlet pipe for each lagoon. The second was simulated with a U shape pipe at the outlet and multiple inlets, it which was constructed in 1995 as part of system improvements. Results from HYDRO-3D program showed that original design had short-circuited and dead zone around of inlet area due to uneven shear stress. Second series of runs to facultative lagoons (Al. B l. C 1). showed that a U shape pipe placed at outlet eliminated a conflictive zone and hence improved mixing within the basin. Wind effects produced more damaged on maturation pond when inlet is placed at the bottom level (current) in comparison with one on the top level (simulated). HYDRO-3D simulation suggested that to increase mixing on maturation ponds A2 and B2 a double directly pipe at the top level would increase hydraulic performance.